Perceived Mate Scarcity Leads to Increased Willingness to Mate Poach. Issue 3 (24th March 2023) - McKelvie, Larissa; Locke, Ashley; Albert, Graham; Minor, Mackenzie; MacKinnon, Megan; Hodges-Simeon, Carolyn; Arnocky, Steven
ABSTRACT: Mate poaching, where an individual attempts to attract a pair-bonded individual, is a risky mating tactic. Yet, it is surprisingly common. Although many studies have investigated individual differences in mate poaching, few have examined potentially relevant ecological factors, such as mate availability. In this study, 254 unmated North American adults were primed with either perceived mate scarcity or abundance, and subsequently completed measures of fear of being single, intrasexual competitiveness, and attitudes toward mate poaching. Results from a sequential mediation model revealed that men and women primed with mate scarcity held a more positive attitude toward mate poaching relative to those primed with mate abundance, and that this link was mediated by an induced fear of being single and intrasexual competitiveness. Our results suggest that mate poaching is a facultative adaptation of human mating psychology driven by intrasexual competitiveness that is activated in response to environments of low mate availability. It highlights the need for researchers to consider ecological cues when studying individual variation in mate poaching behavior.